Hubungan Gejala Klinis dengan Neutrofil-Limfosit Rasio (NLR) pada Anak dengan Covid-19 di Rumah Sakit H.Abdul Manap Kota Jambi - Okto Dolin Hutabarat; Fransiska Farah (Majalah Kedokteran Andalas, 2023)
This research was conducted with the aim of knowing the relationship between clinical symptoms and NLR in children with COVID-19 at H. Abdul Manap Skripsi Genap 2021/2022 2 Hospital, Jambi City. The research method is a correlative analysis study with a cross-sectional descriptive design using data in the form of secondary medical records of COVID-19 pediatric patients treated in isolation rooms for the period January - July 2021. male (55.1%), with a mild clinical degree (87, 7%) and NLR < 3.13 (98%). Calculation of NLR is based on the clinical degree obtained in both mild clinical degrees and the majority of NLR <3.13 (87,7% and 1,9% 10,4%). This study showed a weak correlation (r=0.386; p value=0.006 (p<0.05)) between mild and moderate clinical degrees and Neutrophil-Lymphocytes in children with confirmed COVID-19 at H. Abdul Manap Hospital, Jambi City.